Pediatric multifocal liver lesions evaluated by MRI - Majed Almotairi; Kamaldine Oudjhane; Govind B Chavhan (Indian Journal of Radiology and Imaging, 2015)
Objective: The purpose of this study is to present our experience with MRI evaluation of multifocal liver lesions in children and describe the MRI characteristics of these lesions. Patients and Methods: A retrospective review of consecutive MRI exams performed for the evaluation of multiple liver lesions between 1 January 2007 and 31 December 2012 was done to note the number of lesions, the size of the largest lesion, MR signal characteristics, and background liver. Final diagnosis was assigned to each case based on pathology in the available cases and a combination of clinical features, imaging features, and follow-up in the remaining cases. Results: A total of 48 children (22 boys, 26 girls; age between 3 months and 18 years with average age 10.58 years and median age 11 years) were included in the study. Totally 51 lesion diagnoses were seen in 48 children that included 17 focal nodular hyperplasia (FNH), 8 hemangiomas, 7 metastases, 6 regenerative nodules, 3 adenomas, 3 abscesses, and one each of angiomyolipoma, epithelioid hemangioendothelioma, focal fatty infiltration, hepatocellular carcinoma, hepatic infarction, nodular regenerative hyperplasia, and hepatic cyst. Background liver was normal in 33, cirrhotic in 10, fatty in 3, and siderotic in 2 children. Most FNH, hemangiomas, and regenerative nodules showed characteristic MRI features, while metastases were variable in signal pattern. Conclusion: Many commonly seen multifocal liver lesions in children have characteristic MRI features. MRI can help to arrive at reasonable differential diagnoses for multifocal liver lesions in children and guide further investigation and management.